RANCANG BANGUN PLATFORM WEB E-COMMERCE UNTUK MENDUKUNG BISNIS (STUDI KASUS : TOKO JAKARTA DECOR) - Muhammad Aulia AlHafiz; Muhammad Furqoon Khalilullah; Fitriani Sundari; Najla Khairunnisa; Arya Ridho Pratama; Muhammad Hafizh; Serly Marta Gustika; Wide Mulyana (Universitas Ivet, 2025)
Businesses, especially those in the decoration industry, have been forced to move to online-based systems by the development of digital technology. Jakarta Decor Store struggled to reach a wider audience and improve transaction effectiveness. The goal of this project was to create an online e-commerce platform that would allow the company to better handle orders, payments, and merchandise. Requirement analysis, system design, implementation, and testing are all phases of the waterfall development methodology. The application’s data structure and flow are described by the system architecture using entity relationship diagrams (ERDs), use case diagrams, and class diagram approaches. The output of this study is a web platform that allows users to manage orders, make online purchases, and choose from a variety of payment options. The system operates according to its intended specifications, as demonstrated by testing using black box testing techniques. It is expected that the implementation of this system will improve market accessibility, enhance operational effectiveness, and facilitate consumer transactions.